Impact of loneliness and social isolation on the cognition of healthy adults: a systematic review - Arana-Nombera , Harold Alessandro (2025)
Loneliness and social isolation are factors that increasingly affect many people around the world, and evidence suggests that they are related to cognitive processes deterioration. This article aims to review the available information on the effect of loneliness and social isolation on the cognition of middle-aged adults. A comprehensive structured search was conducted in PubMed, Scopus, Web of Science and EBSCO databases. In the first instance, the results of the databases were imported to the Mendeley reference manager, where duplicates were eliminated, to later extract articles relevant to the topic according to the title and abstract. The inclusion criteria included only articles published in English, conducted in humans, and published within the last ten years (2012-2022). Persistent loneliness was found to be associated with lower cognitive scores and reduced volumes in the temporal lobe and hippocampus, as well as enlarged lateral ventricles. However, when factors such as age, depressive symptoms, and the presence of the APOE ε4 allele were considered, the strength of these associations tended to diminish. A similar pattern was observed when loneliness and social isolation co-occurred, though this was not the case for social isolation alone. It is concluded that loneliness, more than social isolation, appears to be associated with poorer cognitive functioning, whether considered independently or in combination with social isolation, compared to individuals not exposed to these factors. Nonetheless, these findings should be interpreted with caution, as various intervening or moderating variables may influence this relationship. Further research focused specifically on middle-aged populations is needed to clarify the nature and mechanisms of these associations.